Faktor-Faktor Yang Berhubungan Dengan Loyalitas Pelanggan Di Instalasi Rawat Jalan UPTD Rumah Sakit Tipe C Manembo-Nembo Bitung - Fista Fella Kipu; Windy M.V. Wariki; Alexander S.L. Bolang (Universitas Sam Ratulangi, 2021)
Background: Attitudes and actions of doctors, nurses, administration as well as inaction in services, drug supplies, inadequate infrastructure and medical equipment are still problems that become complaints by service users. Hospitals must have the ability to attract and retain customers who do not only come from the product or service itself. The purpose of this study was to analyze the factors related to customer loyalty in the outpatient installation of the UPTD Hospital Type C Manembo-nembo Bitung. Methods: This research is an observational study with a cross sectional study design. A total of 100 outpatients who have received health services at the UPTD Outpatient Installation of Type C Hospital, Manembo-nembo Bitung participated in this study. Data were analyzed using univariate, bivariate and multivariate and logistic regression statistical calculations. Presentation of data is made in table and narrative form. Results: The results showed that a significant relationship between products and customer loyalty with a value of p = 0.024, between processes and customer loyalty with a value of p = 0.000, between location and customer loyalty with a value of p = 0.061, between promotion and loyalty with a value of p = 0.435 , between employees with loyalty with a value of p = 0.000, between physical evidence and loyalty with a value of p = 0.005. However, there is no promotion relationship with loyalty. The results of the mutivariate analysis showed that the product factor was the most dominant factor influencing the loyalty of outpatients at Manembo-nembo Hospital Type C Bitung.Conclusion: This research can be conclude that the process factors are the most dominant factors related to customer loyalty in the Outpatient Polyclinic of the UPTD Type C Hospital, Manembo-nembo, Bitung.